2022
DOI: 10.1021/acs.jpcc.2c03175
|View full text |Cite
|
Sign up to set email alerts
|

Ion Migration in the All-Inorganic Perovskite CsPbBr3 and Its Impacts on Photodetection

Abstract: Ion migration has been widely investigated in the lead halide perovskites, which severely deteriorates the performance of solar cells. However, the impacts of ion migration on photodetection have been rarely studied so far. In the current work, ion migration in the all-inorganic perovskite CsPbBr3 and its impacts on photodetection have been investigated in detail. Electrical property studies showed that ion migration has occurred under an external electric field poling, which led to the formation of a pn-junct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…Due to the top-contact device structure, the gold electrodes are thinner at the side of the NW, so that the scattered light from the laser spot may be collected by the Au-NW Schottky junction. As Br anions have been identified as the mobile ions in CsPbBr 3 , 38 the positively charged ions are likely Br vacancies, which accumulate near the cathode. The concentration of accumulated vacancies can alter the local Fermi energy level, 26 resulting in significant band bending and strong internal electric field (Figure 2d).…”
Section: Resultsmentioning
confidence: 99%
“…Due to the top-contact device structure, the gold electrodes are thinner at the side of the NW, so that the scattered light from the laser spot may be collected by the Au-NW Schottky junction. As Br anions have been identified as the mobile ions in CsPbBr 3 , 38 the positively charged ions are likely Br vacancies, which accumulate near the cathode. The concentration of accumulated vacancies can alter the local Fermi energy level, 26 resulting in significant band bending and strong internal electric field (Figure 2d).…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, it is known that the chemical bonding strength between the Cs + cation in the perovskite crystal structure with the [PbBr x ]the framework is weak, and the energy barrier for migration of Cs + in the perovskite crystal structure is 0.3-0.7 eV [42][43][44] . Experimental evidence has shown that Cs + can drift away from the perovskite crystal structure under certain electrical fields which are high enough to overcome the energy barrier for Cs + migration.…”
Section: Understanding the Cycle Stability Of The Cspbbr 3 Electrodementioning
confidence: 99%
“…Cation doping, small molecule or polymer addition, and low dimensional perovskites have been reported to strengthen the crystal structure, improve the crystalline quality, and enhance the moisture and thermal resistance, thus suppressing ion migration. [139][140][141][142] Ma et al presented that both polymers of poly [4,8-…”
Section: Inhibiting the Ion Migrationmentioning
confidence: 99%
“…Cation doping, small molecule or polymer addition, and low dimensional perovskites have been reported to strengthen the crystal structure, improve the crystalline quality, and enhance the moisture and thermal resistance, thus suppressing ion migration. [ 139–142 ] Ma et al. presented that both polymers of poly[4,8‐bis(5‐(2‐ethylhexyl)thiophen‐2‐yl)benzo[1,2‐b;4,5‐b′]dithiophene‐2,6‐diyl‐alt‐(4‐(2‐ethylhexyl)‐3‐fluorothieno[3,4‐b]thiophene‐)‐2‐carboxylate‐2‐6‐diyl)] (PCE10) with a large dipole moment of 3.7D and PS with a small dipole moment of 0.6D restricted ion movement and improved the device stability ( Figure a).…”
Section: A Perovskite–polymer Composite For High‐performance Perovski...mentioning
confidence: 99%